Analysis of Factors Affecting Inpatient Satisfaction at RSU Wulan Windy Medan Marelan - Sihombing, Sartika Dewi; Nasution, Siti Khadijah; Zulfendri, Zulfendri (Formosa Journal of Applied Sciences, 2024)
Patient satisfaction is a key indicator in assessing the quality of healthcare services provided by hospitals. It reflects the individual experiences of each patient and signifies the effectiveness of the service delivery system. High levels of satisfaction are associated with timely service delivery, environmental comfort, effective communication, and the expertise and friendliness of medical staff. This study analyzes factors influencing inpatient satisfaction at RSU Wulan Windy Medan Marelan. The research employs a quantitative approach through survey methodology with data collected from 355 respondents. Statistical analysis included bivariate chi-square tests and multivariate logistic regression. Results indicate significant impacts of timely service delivery, comfort, and staff competence on patient satisfaction, with p-values of <0.001 for each factor.